Food security: does it matter? / Irlisuhayu Mohd Ramli and Nabila Ahmad - Mohd Ramli, Irlisuhayu; Ahmad, Nabila (Universiti Teknologi MARA, Kedah, 2023)
According to the United Nations’ Committee on World Food Security, food security refers to the state in which all people, at all times, have physical, social, and economic access to sufficient, safe, and nutritious food that meets their dietary needs and preferences for an active and healthy life. Strengthening the food system is vital in ensuring the provision of nutritious food and preserving environmental sustainability. Food security is crucial for a nation as it is closely related to population growth, food safety, malnutrition, food accessibility, and resource sustainability. Population growth has been identified as a threat to food security by several studies (Kwasek, 2012; Vásquez et al., 2018; Smith & Archer, 2020; Molotoks et al., 2021). According to the latest projections by the United Nations (2022), the world's population could increase to approximately 8.5 billion by 2030 and 9.7 billion by 2050. The population is expected to peak at 10.4 billion people in the 2080s and remain at that level until 2100. This rapid population growth is expected to drive up the demand for food, making it more challenging to achieve food security in terms of availability and accessibility.